2001
DOI: 10.1039/b109427k
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal-based enzyme-linked immunosorbent assay and immunochromatographic assay for enrofloxacin in biological matrices

Abstract: Enrofloxacin has been increasingly used in veterinary medicine to treat microbial infections. A simple and reliable analytical method for this drug is required. The current determination by high performance liquid chromatography (HPLC) is sensitive but labor-intensive. This paper reports an enzyme-linked immunosorbent assay (ELISA) using a monoclonal antibody (MAb) and the development of a rapid test kit based on immunochromatography. The detection limits using the ELISA were 10 ppb for chicken liver and muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 15 publications
8
53
0
Order By: Relevance
“…Numerous studies have been reported on developing ELISA methods for the detection of FQs, including CPFX (Mellgren and Sternesjö, 1998), enrofloxacin (Mellgren and Sternesjö, 1998;Watanabe et al, 2002), norfloxacin (Watanabe et al, 2002;Huet et al, 2006), pefloxacin (Mellgren and Sternesjö, 1998;Huet et al, 2006), and sarafloxacin (Lu et al, 2006). Moreover, Bucknall et al (2003) reported results concerning a polyclonal antibody against CPFX with a limit of detection (LOD) of 4 ng/ml (Bucknall et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported on developing ELISA methods for the detection of FQs, including CPFX (Mellgren and Sternesjö, 1998), enrofloxacin (Mellgren and Sternesjö, 1998;Watanabe et al, 2002), norfloxacin (Watanabe et al, 2002;Huet et al, 2006), pefloxacin (Mellgren and Sternesjö, 1998;Huet et al, 2006), and sarafloxacin (Lu et al, 2006). Moreover, Bucknall et al (2003) reported results concerning a polyclonal antibody against CPFX with a limit of detection (LOD) of 4 ng/ml (Bucknall et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of our method is comparable to ELISA and electrophoresis, and may not have an advantage over routine analytical methods such as HPLC, LC/MS, and ELISA in terms of sensitivity. [12][13][14][15][16][17][18][19][20][21][22][23] However, our approach is advantageous over these methods since it has a short assay time, a simple experimental protocol, and low background signals. We believe that our strategy has wide potential for use as a detection method for small molecules that have corresponding antibodies or capturing agents.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] A number of countries have therefore regulated the use of these two FQs for animal bred for food production; for example, the European Union and the United States have set maximum residue limits (MRLs) in edible tissues, milk, and eggs, and the use of these two drugs is restricted for laying hens. [9][10][11] Along with tightening up the regulations on FQ use, various analytical methods have been developed for determining or screening FQ residues, including high-performance liquid chromatography (HPLC), [12][13][14] liquid chromatography-mass spectrometry (LC/MS), 15,16 enzyme-linked immunosorbent assays (ELISA), [17][18][19][20] and capillary electrophoresis. [21][22][23] Although these methods are routinely used with high sensitivity, general use of these methods is sometimes hampered by the need for sophisticated and time-consuming processes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the farthest parts of the M3 molecular structure coupling site (hapten and the carrier protein) are the same as TBBPA DHEE and TBBPA MHEE. According to the rule in immunology (Bucknall et al, 2003;Watanabe et al, 2002;Zhang et al, 2013), antibodies elicited from haptenic conjugates showed a preferential recognition to the molecule part that was farthest from coupling site. In this study, TBBPA DHEE and TBBPA MHEE (the structures of both chemicals are shown in Fig.…”
Section: Preparation Of Hapten M3 Its Conjugates and Antibodymentioning
confidence: 99%